Keputusan Investasi Digital dan Pendanaan Berbasis Kinerja Dalam Memperkuat Tata Kelola Smart Governance - Sitti Murniati; Herlina (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2026)
This study aims to analyze the relationship between digital investment decisions and performance-based funding in strengthening smart governance in Makassar City. The research employs a qualitative descriptive method with a public policy case study approach, using in-depth interviews, field observations, and document analysis of digital governance programs such as Makassar Sombere & Smart City and the Command Center. The findings indicate that digital investment decisions have a positive impact on enhancing transparency and efficiency in public services, although challenges remain due to a predominantly top-down decision-making process and limited inter-agency system integration. Performance-based funding has improved budget accountability, yet performance indicators remain focused on administrative outputs rather than service outcomes. The synergy between digital investment and performance-based funding strengthens the effectiveness of smart governance through data-driven supervision and participatory management. The study recommends reinforcing evidence-based decision-making mechanisms, improving digital competency among civil servants, and developing outcome-based evaluation systems to achieve sustainable smart governance in Makassar City.